Potential Echinodermata in Samboang Beach Bulukumba District as a Source of Biodiversity Learning - Angraeni, Andi Tirta; Arsal, Andi Faridah; Saleh, Andi Rahmat (Biology Teaching and Learning, 2024)
This research aims to find out what echinodermata can be found on Samboang Beach in Bulukumba district that can be used as a source of learning outside the classroom. This research uses a type of qualitative descriptive research. The research instruments used in this study are the observation sheet and identification sheets. Based on observations and data identification, it can be concluded that "Inventarization of Echinodermata at Samboang Beach in Bulukumba district as a source of learning outside the classroom" is: The type of echinoderma found in Samboanga Beach is that there are 8 species, 7 genus, 7 families, and 6 ordos, consisting of 4 classes of the filum echinoderma.Keywords : Inventory, Echinoderms, Learning Resources